2014
DOI: 10.1186/1479-5876-12-112
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic function of tumor-associated antigen RCAS1 in oral squamous cell carcinoma

Abstract: BackgroundReceptor-binding cancer antigen expressed on SiSo cell (RCAS1) is derived from uterine adenocarcinoma and can induce apoptosis in lymphocytes, allowing tumor cells to escape from immune surveillance. RCAS1 is reportedly expressed in a membranous pattern on tumor cell or soluble one in serum of patients. The aim of this study was to investigate expression patterns of RCAS1 and the effect on apoptosis in oral squamous cell carcinoma (OSCC) cell lines.MethodsIn four kinds of OSCC cell lines (HSC-2, HSC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…NA cell line was established as a fibronectin-producing cell line (14). Furthermore, it has been reported that the cytotoxicity of anti-cancer reagents in OSCC has been evaluated in SQUU-A cell line and SQUU-B cell line (15), SAS cell line (16), NA cell line (17) using various conventional methods. That is why, we selected four these cell lines with each characteristic feature in the present study, which were also used in cytotoxic assay in previous study.…”
Section: Introductionmentioning
confidence: 99%
“…NA cell line was established as a fibronectin-producing cell line (14). Furthermore, it has been reported that the cytotoxicity of anti-cancer reagents in OSCC has been evaluated in SQUU-A cell line and SQUU-B cell line (15), SAS cell line (16), NA cell line (17) using various conventional methods. That is why, we selected four these cell lines with each characteristic feature in the present study, which were also used in cytotoxic assay in previous study.…”
Section: Introductionmentioning
confidence: 99%